France : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This 2013 Article IV Consultation highlights that in a context of weakening economic conditions in Europe and sizeable fiscal consolidation and domestic policy uncertainty, the French economy flat lined in 2012. However, recent improvements in economic indicators support the expectation of a gradual recovery in the second half of 2013. Credit conditions remain supportive, and private demand is unencumbered by balance sheet repair issues and thus more apt to respond favorably to an improvement in confidence. The economy is projected to contract by 0.2 percent in 2013 and to grow by 0.8 percent in 2014.